2011
DOI: 10.1002/pts.981
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of a New Antimicrobial Active Packaging for Fresh Atlantic Salmon (Salmo Salar L.) Shelf Life

Abstract: Nowadays, consumers demand for fresh, high‐quality seafood products continues to climb, especially in affluent, developed nations. At the same time, there is increasing attention regarding improved utilization of seafood for human consumption; Atlantic salmon is the main species in Chile aquaculture, and most of the salmon are exported as fresh fish to USA. It is well documented that low storage temperature inhibit bacterial growth and biochemical degradation, thus facilitating prolonged shelf life. Partly fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
(62 reference statements)
3
27
1
Order By: Relevance
“…In addition, the losses may have been caused by the chemical instability of eugenol in the presence of air, light, oxygen and other environmental factors. Suppakul et al, [38] reported higher losses of antimicrobial agents, such as linalool and methylchavicol from LDPE and ethylene vinyl acetate (EVA) than those observed in the present study; after the blowing process, the authors observed a concentration of 0.34 g/100 g, down from an initial concentration of 1.0 g/100 g. Galloto et al, [39] reported that nearly 30% of the thymol initially included in a formulation of antimicrobial low density polyethylene (LDPE) film remained after the extrusion process. Yuwono et al [27], reported that the vapor pressure of eugenol increases from 0.01 mm Hg at 20°C to 20 mm Hg at 138.7°C; therefore, losses of eugenol were influenced by evaporation into the environment due to the high volatility of eugenol at processing temperatures.…”
Section: Discussioncontrasting
confidence: 40%
“…In addition, the losses may have been caused by the chemical instability of eugenol in the presence of air, light, oxygen and other environmental factors. Suppakul et al, [38] reported higher losses of antimicrobial agents, such as linalool and methylchavicol from LDPE and ethylene vinyl acetate (EVA) than those observed in the present study; after the blowing process, the authors observed a concentration of 0.34 g/100 g, down from an initial concentration of 1.0 g/100 g. Galloto et al, [39] reported that nearly 30% of the thymol initially included in a formulation of antimicrobial low density polyethylene (LDPE) film remained after the extrusion process. Yuwono et al [27], reported that the vapor pressure of eugenol increases from 0.01 mm Hg at 20°C to 20 mm Hg at 138.7°C; therefore, losses of eugenol were influenced by evaporation into the environment due to the high volatility of eugenol at processing temperatures.…”
Section: Discussioncontrasting
confidence: 40%
“…AP system can be defined as a system in which the food product, the packaging material, and the headspace between the package and the food interact with the intention to extend shelf‐life while maintaining quality, freshness, and safety of the food . Antimicrobial (AM) packaging is a form of active packaging, in which AM agents are added directly to the packaging material instead of being directly added to food, preventing the surface growth of pathogenic microorganisms . There are generally three techniques used to achieve AM active packaging: (1) absorption (2) immobilization, and (3) release system.…”
Section: Introductionmentioning
confidence: 99%
“…Most EOs are approved for contact with food and are classified as generally recognized as safe by the US Food and Drug Administration . Various studies have already evaluated the implementation of various EOs for food‐packaging applications, such as thymol, carvacrol, linalool, methylchavicol, oregano, citral, cinnamaldehyde, basil, and rosemary in different polymer matrices . Thymol is a component found in EOs of thyme and oregano that has received substantial attention as a possible natural AM agent and as a possible food antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…As Table 1 shows, after extrusion, extraction procedures revealed final concentrations of thymol in the film between 40-80 % of thymol that was initially included in the films formulation. Several studies showed similar or higher losses of some volatile active agents due to stress and high temperature conditions during extrusion process 29,30 . Concentration of thymol in the films over time (Figure 1) was also measured owing to quantify their activity during storage time, and maybe to estimate these films´ shelf life.…”
Section: Quantification Of Thymol Effective Concentration In Lldpe Namentioning
confidence: 96%
“…The nanocomposite spectrum presented the presence of bands in the zone of absorption of the silicate groups between 900 -1100 cm -1 confirming the incorporation of the nanoclays in LLDPE matrix ( Figure 5). Exactly the bands found were at 460 cm -1 (Si-O-Si bending), 520 cm -1 (Si-OAl bending), 1040 cm -1 (Si-O stretching), and at 1075 cm -1 (-OH bending from absorbed water) [27][28][29][30][31][32][33][34][35] . In the case of active materials, it is possible to observe the characteristic bands for thymol, at 730 and 805 cm -1 owing to ring vibrations of aromatic groups 36 .…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%